Effect of Goods and Services Procurement Management with Direct Selection Method on PT Sumberbumi Global Niaga Ship Operations - Conitia Erlina Muftiati Ahmad; Sugiyanto Sugiyanto; Laila Puspitasri; Titis Ariwibowo (Greenation International Journal of Economics and Accounting, 2023)
PT Sumberbumi Global Niaga is engaged in services, namely shipowners whose ships owned by the company are leased to cargo owners. So that the shipping fleets are proof that there has been an opportunity to develop the shipping business. In line with the development of the shipping business, good operational performance is very much needed in a shipping company considering the increasingly competitive field. Based on the data, the existing problems discuss the management of procurement of goods and services, the method of direct selection of operations. The purpose of this study was to determine how much influence and management of the procurement of goods and services with the direct selection method together on ship operations. In this study found the results of data from the influence of the management of procurement of goods and services with the direct selection method together on ship operations. For this shipping company, it is necessary to pay attention to things that encourage the creation of time optimization in the provision of spare parts as feedback from the company in order to achieve ship operational targets.